IMPLEMENTASI APLIKASI PENJADWALAN MATAKULIAH PROGRAM STUDI INFORMATIKA BERBASIS WEBSITE - Wayan Farel Nickholas Sadewa; Luh Gede Astuti; Anak Agung Istri Ngurah Eka Karyawati (Jurnal Pengabdian Informatika, 2026)
Scheduling courses in the Informatics Program of the Faculty Scheduling courses in the Informatics Program of the Faculty of Mathematics and Natural Sciences, Universitas Udayana, is very crucial for optimizing resources like classroom spaces, and instructor time. However, manual scheduling consuming so much time and is prone to errors, which can lead to scheduling conflicts between courses, instructors. and rooms. This study aims to develop a web-based course scheduling application that's efficient and accessible to the staff. The methods used include situation analysis, problem formulation, interface design, and system implementation. The implementation result shows that the application simplifies the scheduling process and reduces the risk of scheduling conflicts. This system is expected to improve efficiency of scheduling in the Informatics Program at Universitas Udayana.